Estimating tactical surface metering management’s effect on aircraft fuel savings at airport - Fukui, Hideki; Miyoshi, Chikage (Elsevier, 2024)
We estimated the effect of surface metering technology deployed at Charlotte Douglas International Airport (CLT) by the National Aeronautics and Space Administration (NASA) and the Federal Aviation Administration (FAA) on fuel and CO2 savings. We employed a difference-in-differences strategy, covariate-balancing methods, and a fixed-effects model. Furthermore, we used a doubly robust strategy that combines matching with parametric regression using datasets constructed by data-driven approaches, which minimizes discretion in selecting comparison units. Our estimates from the daily panel of US carriers from November 2015 to November 2019 suggested that about 39.156 kg (95% confidence interval (CI) 64.017–13.436) of fuel and 120.599 kg (CI 197.174 kg–41.382 kg) of CO2 could be saved per flight even when the single-engine taxiing rate was as high as 75% during the entire deployment phase. At the same time, our results suggested a concerning pattern: taxi-out time savings generated by the technology diminished over time.
Keywords: Tactical surface metering; Taxi-out/in fuel consumption; Terminal flight data manager; Difference-in-differences; Propensity score matching